A Software Suite for Limb Volume Analysis Applicable in Clinical Settings: Upper Limb Quantification - Nascimben, Mauro; Lippi, Lorenzo; Fusco, Nicola; Invernizzi, Marco; Rimondini, Lia (Frontiers in Bioengineering and Biotechnology, 2022)
In medicine, tridimensional scanning devices produce digital surfaces that replicate patients’ bodies, facilitating anthropometric measurement and limb volume quantification in pathological conditions. Free programs that address this task are not commonly found, with doctors mainly relying on proprietary software. This aspect brings reduced reproducibility of studies and evaluation of alternative measures. A software package made up of three programs has been developed and released together with supporting materials to enhance reproducibility and comparisons between medical centers. In the present paper, the functions of the programs and steps for volume assessment were introduced together with a pilot study for upper limb volume quantification. This initial experiment aimed to verify also the performance of digital volumes derived from the convex hull gift wrapping algorithm and the alternative analysis methods enclosed in the software. Few of these digital volumes are parameter-dependent, requiring a value selection. The experiment was conducted on a small mixed-gender group of young adults without correction for factors like arm dominance or specific physical training. In the sample under investigation, the analysis confirmed the substantial agreement between the clinical and current configuration of digital volumes produced by the package (R square interval from 0.93 to 0.97, r ranged from 0.965 to 0.984); in addition, as a general consideration, gender appears as a variable that could influence upper limb volume quantification if a single model is built.